DISEMINASI KOLEKSI LOKAL: PEMBANGUNAN REPOSITORI INSTITUSI PERPUSTAKAAN KEMENTERIAN PENDIDIKAN DAN KEBUDAYAAN - Chaidir Amir; Riche Cynthia Johan (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2019)
The Ministry o Education and Culture Library s a special library  as a deposit center that performs the fungtions of  collecting and storing all publications form and about its parent institution. Until 2016, the Ministry of Education an Culture had not yet devoleped a systematically integrated and managed information/database system of internal collection so as to dissaminete public information to the public. The development program that can be carried out so as to build and integrsted information/database system of internal collection is the development of institutional  repository. The development of this institusi  institusional repository aims to collect, store, manage, preserve and dissaminete the institution’s internal publications. Institution’s public documents as well as intellectual properties and researches, all in electronik form, produced bay the ministry human resources, as a unit within the  institution, has a reponsibility an plays a key role in building  this institutional repository. Library is a unit that performs teh functians of collecting, storing, managing, perserving and dissamminating institution’s  intellectual properties. Librarians will properly  manage the development  of the institutional repository are as follows : 1) Library data in the ministry has been updated using  the ministry library directory application. A total of 96 libraries within the ministry have submitted their data to the library directory application; 2) The types of internal collections within the Ministry have been mapped and become material in preparation of the institutional repository policy of the ministry; 3) The institutional repository policy of the Ministry has been prepared and is expected to be a guide for parties involved in the operational activities of institutional repository; 4) The institutional repository of the Ministry has been instaled and can be accessed on the website http://repository.perpustakaan.kemdikbud.go.id: 5) The form letters of printed and Recorded Works (Publications) Handover Obligation of the Ministry; 6) The web research engine which is integrated between institutional repository and library automation system can be accessed throught the Ministry page at http://perpustakaan.kemdikbud.go.id